Investigation of Organosolv Pretreatment to Natural Microbial-Degraded Empty Fruit Bunch for Sugar based Substrate Recovery. (February 2019) - Chin, Danny Wei-Kit; Lim, Steven; Pang, Yean-Ling; Leong, Loong-Kong; Lim, Chun-Hsion
Abstract: Fresh empty fruit bunch is highly susceptible to microbial attack when exposed to the natural environment for pro-long period. This natural microbial-degraded empty fruit bunch or DEFB was discovered to exhibit modestly higher cellulosic contents, reduced ash contents and modestly higher lignin content compared to fresh empty fruit bunch. Higher cellulosic contents extracted using lower pretreatment process severity after natural microbial degradation action had rendered DEFB a promising feedstock for lignocellulosic biofuel production. Pretreatment with 50 v/v% ethylene glycol in the presence of 3 v/v% NaOH performed the best result with 67.2% delignification and 90.6% alpha cellulose recovery. Pretreatment with 50 v/v% ethylene glycol in the presence of 5 v/v% H2 SO4 and 5 v/v% FeCl3 were able to degrade alpha cellulose considerably. This information would be vital for the subsequent hydrolysis process to optimize the yield of reducing sugar from DEFB.